Risk stratification in adult and pediatric pulmonary arterial hypertension: A systematic review - Lokhorst, Chantal; van der Werf, Sjoukje; Berger, Rolf M. F.; Douwes, Johannes M. (Frontiers in Cardiovascular Medicine, 2022)
Introduction Currently, risk stratification is the cornerstone of determining treatment strategy for patients with pulmonary arterial hypertension (PAH). Since the 2015 European Society of Cardiology/European Respiratory Society (ESC/ERS) guidelines for the diagnosis and treatment of pulmonary hypertension recommended risk assessment, the number of studies reporting risk stratification has considerably increased. This systematic review aims to report and compare the variables and prognostic value of the various risk stratification models for outcome prediction in adult and pediatric PAH. Methods A systematic search with terms related to PAH, pediatric pulmonary hypertension, and risk stratification was performed through databases PubMed, EMBASE, and Web of Science up to June 8, 2022. Observational studies and clinical trials on risk stratification in adult and pediatric PAH were included, excluding case reports/series, guidelines, and reviews. Risk of bias was assessed using the Prediction model Risk Of Bias Assessment Tool. Data on the variables used in the models and the predictive strength of the models given by c-statistic were extracted from eligible studies. Results A total of 74 studies were eligible for inclusion, with this review focusing on model development (n = 21), model validation (n = 13), and model enhancement (n = 9). The variables used most often in current risk stratification models were the non-invasive WHO functional class, 6-minute walk distance and BNP/NT-proBNP, and the invasive mean right atrial pressure, cardiac index and mixed venous oxygen saturation. C-statistics of current risk stratification models range from 0.56 to 0.83 in adults and from 0.69 to 0.78 in children (only two studies available). Risk stratification models focusing solely on echocardiographic parameters or biomarkers have also been reported. Conclusion Studies reporting risk stratification in pediatric PAH are scarce. This systematic review provides an overview of current data on risk stratification models and its value for guiding treatment strategies in PAH. Systematic review registration [https://www.crd.york.ac.uk/prospero/display_record.php?ID=CRD42022316885], identifier [CRD42022316885].